Impact of long-haul airline travel on athletic performance and recovery: a critical review of the literature - Botonis, P. G.; Toubekis, A. G.; Hill, D. W.; Mündel, T. (Experimental Physiology, 2025)
Participation in many important sport events (e.g., World championships, Olympics) requires athletes to fly >4 h and to cross several time zones. This transmeridian travel results in a transient desynchronization of the body's circadian rhythms due to a disconnect between the timing of the endogenous circadian oscillator and the external stimuli, manifested as `jet lag`. While recent reviews highlight the importance of managing jet lag, the time required for resynchronization of the internal clock and dissipation of jet lag symptoms has not yet been summarized. Further, although the literature reports that rapid transmeridian travel is detrimental for athletes` performance, empirical evidence from studies involving athletes is equivocal. Herein, we summarize the evidence that the variability in responses to transmeridian travel can be attributed to differences in (i) travel (real vs. simulated, westbound vs. eastbound, time zones crossed, during normal waking hours vs. normal sleep time), (ii) testing (assessment of performance vs. factors related to performance), and (iii) timing of the testing (destination time vs. `body time`), and we offer the possibility that differences in (iv) teams, (v) traits, and (vi) tournaments may also be implicated. We focus on (i) aerobic power/endurance, (ii) anaerobic power and capacity, (iii) strength, and (iv) mood state, sleep quantity and quality, and jet lag symptoms in this literature review, which is limited to athletes or physically active participants, travelling west or east crossing four or more time zones.